Implementing OLAP Technology to Leverage Value of Supply Chain Management System - Ekananta, Ekananta (The Asian Journal of Technology Management (AJTM), 2008)
Supply chain refers to the flow of materials, information, money, and services from rawmaterial suppliers, through factories and warehouses, to the end users. The successful of company inthe business competition is highly depend on how well the company capability to optimize andmanage their supply chain process. ERP is an information technology solution that play the mainrole in the supply chain management with the aim to plan, organize, and optimize one or more of thesupply chain’s activities which is concentrate on supply chain efficiency.The recent development of Supply Chain Performance Management (SCPM) Application, theOLAP based information technology solutions, will help supply chain managers to be more effectivein managing supply chain activities due to its capability to provide the planning and controllingfunction to achieve a better operation performance.This paper will describe the role of OLAP technology to leverage value of supply chainmanagement system by complement the ERP functions and also provide the descriptions of thetechnology framework and development methodology for Supply Chain Performance Management(SCPM) Application.Keywords: Supply Chain Management, OLAP, Performance Management